If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(-2x-5)=7x+11
We simplify the equation to the form, which is simple to understand
-2(-2x-5)=7x+11
Reorder the terms in parentheses
+(+4x+10)=7x+11
Remove unnecessary parentheses
+4x+10=+7x+11
We move all terms containing x to the left and all other terms to the right.
+4x-7x=+11-10
We simplify left and right side of the equation.
-3x=+1
We divide both sides of the equation by -3 to get x.
x=-0.333333333333
| y=x^5-4x^4+6x^2-9x+54 | | x^2-4=92 | | x^3-3x^2+12x-36=0 | | 2[b+8]-9=9 | | x^3-3x^2-12x-36=0 | | p=b+3a+2cforb | | 6x-9=99 | | 8[q+7]=-72 | | y=7x^2-4x+2 | | -x^2-x-2=0 | | 10x-9-9=14x-9-9+5x | | 3x-9x-10=-6x+7-10 | | 7s=48 | | 64x^2+8x-8=0 | | (X+45)(x+62)=0 | | 0.5x+1.5=0.8x-0.3 | | 4x+3(2-x)=8 | | 6n+2=72n+9+7 | | 2h+7=46 | | 18x+17=12x+24+6x-7 | | 4x+17=21 | | x^2=-90 | | 8y+2y-12=5+5-4 | | (40-8)/(7)=-z | | (40-z)/(7)=-z | | 6x+6=6x+18 | | 6-7-7= | | (3x+2)(x+1)=x+3 | | x^2+7=-4x | | 8*q+7=-72 | | 2-6(7a-9b)36ab-9= | | 6d-3+2d=5d-8+1 |